Lean tools for sustainability in organizations: an analysis by levels of knowledge and agreement by common sense - Figueiredo, Oydil Cesar de; Oliveira, Ualison Rébula de; França, Sérgio Luiz Braga; Fernandes, Vicente Aprigliano; Lemos, Washington de Macedo (Revista de administração da UFSM, 2025)
Purpose: Investigate the differential perceptions of distinct groups, both with and without knowledge of lean and sustainability, and compare them with the responses of Toyota experts, aiming to identify the agreements and divergences in the evaluations of lean manufacturing tools concerning the three pillars of sustainability: social, environmental, and economic. Methodology: A literature review involving 131 articles was conducted, resulting in the identification of 40 lean manufacturing tools described as having an impact on sustainability. This was followed by exploratory research, employing a self-administered online questionnaire, and comparing results between groups to identify convergent responses. Findings: The findings demonstrate that all groups provided identical responses for 26.4% of the possible answers. Specifically focusing on the group of experts, an increase to 8.3% in unique responses was observed. In the non-expert group, only 0.6% of responses specific to this group and Toyota were added. Practical implications: Gaining an understanding of lean tools that impact sustainability represents a valuable outcome. However, identifying which perspectives align with Toyota's opens new avenues for discussion and research. Originality/Value: Much of the research explores the implementation of lean tools based on the views of experts alone. Yet, no studies have been found comparing the influence of the dissemination of these tools through common sense, thereby allowing for responses that are equivalent to Toyota's.